Application of BATMAN and BAYESIL for quantitative 1H-NMR based metabolomics of urine: discriminant analysis of lean, obese,and obese-diabetic rats - H., Maulidiani; ., Rudiyanto; Mediani, Ahmed; Khatib, Alfi; Ismail, Amin; Hamid, Muhajir; Lajis, Nordin; Shaari, Khozirah; Abas, Faridah (SpringerLink, 2017)
Introduction: BATMAN and BAYESIL are software tools, which can provide a solution for automated metabolite quantifications based on the proton nuclear magnetic resonance (1H-NMR) spectral data of bio-fluids. However, their specific application for the quantitative 1H-NMR based metabolomics of urine has not been investigated.